Aplication Chitosan Modified Carboxymethyl as Antibacterial Agent of Paper Packaging (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2023)
Chitosan and chitosan modified carboxymethyl were used to enhance performances of paper packaging. Chitosan 1.0 wt% and chitosan modified carboxymethyl solutions with concentrations of 0.25; 0.5 and 1.0 wt% were manually applied on paper surface using dip coating method. Effects of chitosan coatings on antibacterial properties of the paper were investigated. The antimicrobial activity of chitosan against gram-positive (Staphylococcus aureus) and gram-negative bacteria (Escherichia coli) was found to be enhanced when chitosan and chitosan modified carboxymethyl solution were entrapped within paper. Further paper coated chitosan and chitosan modified carboxymethyl has higher antibacterial activity againt S. aureus rather than E. coli.Keywords: Chitosan carboxymethyl, antibacterial agent, paper packaging